De l’interprétation systémique du projet de réhabiliter un bâtiment - Cantin, Richard; Cryonnet, Jean-Claude (Acta Europeana Systemica, 2020)
The target of retrofitting project only cannot be to retrofit a building. It must also modify the building integrating the new constraints of sustainable development, the energy model transition and climate change. Thus, for several years, the environment of retrofitting projects become more complex, and for reaching the highest levels of energy and environmental performance during the rehabilitation of an existing building, it is necessary to consider the complexity of the retrofitting action. In this context, a project can be viewed as a system of actions in order to convert or refurbish the building system. This interpretation is based on concepts of the systemic approach and on a generic representation with a combination having presided at the project invention. The structural and functional approaches provide a generic representation of a distanced and global view of the complexity of the retrofitting project, which as a system evolves along a path combining anticipation, caesura and virtualization. In this paper, the complex environment of the retrofitting project is presented. Different concepts of the systemic approach used to deal with the complexity of the retrofitting project are described. A chronicle of project allows to elaborate a generic representation of project. Finally, this representation is complemented by elements of systemic modeling for differently interpreting the retrofitting project.